2020
DOI: 10.1097/md.0000000000023299
|View full text |Cite
|
Sign up to set email alerts
|

Interactive associations of sex and hyperlipidemia with calcific tendinitis of the shoulder in Taiwanese adults

Abstract: Calcific tendinitis (CT) of the shoulder is a painful disorder usually identified in individuals aged 40 and 60 years. The estimated global prevalence of CT is 2.7% to 36%. We examined the association of hyperlipidemia and sex with CT of the shoulder using Taiwan Biobank (TWB) and the National Health Insurance Research Database (NHIRD). Data were available for 9903 TWB participants who were recruited between 2008 and 2015. We used multiple logistic regression analysis to estimate the odds ratios (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Hyperlipidemia, a systemic metabolic disorder, has adverse effects on the cardiovascular and musculoskeletal systems. The mechanical properties of tendons are reduced by excessive accumulation of lipids in the extracellular matrix, and fatty infiltration can impair post-surgical tendon-bone healing and clinical outcomes [ 3 ]. A significantly higher incidence of calcific tendinitis was reported after 11 years of follow-up in patients with hyperlipidemia by Lin et al Meanwhile, treatment of hyperlipidemia served as an effective protective factor against RCCT [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia, a systemic metabolic disorder, has adverse effects on the cardiovascular and musculoskeletal systems. The mechanical properties of tendons are reduced by excessive accumulation of lipids in the extracellular matrix, and fatty infiltration can impair post-surgical tendon-bone healing and clinical outcomes [ 3 ]. A significantly higher incidence of calcific tendinitis was reported after 11 years of follow-up in patients with hyperlipidemia by Lin et al Meanwhile, treatment of hyperlipidemia served as an effective protective factor against RCCT [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the current literature, it is known that CT is frequently seen between the ages of 30 and 50. 2,15 In our study, the mean age of patients diagnosed with CT was found to be 57.40 ± 11.27 years. This may be due to the fact that we included patients with a diagnosis of CT who had a lipid profile at the time of admission and that young patients generally do not have a regular lipid profile, and middle-aged or elderly patients regularly have their lipid profile checked.…”
Section: Discussionmentioning
confidence: 51%
“…However, no published study has discussed the association between these comorbidities and calcific tendinopathy, except for one nationwide population-based matched cohort study, which found that hyperlipidaemia increases the risk of calcific tendinopathy of the shoulder, compared with non-hyperlipidaemia. 15 Abboud et al 29 also discovered that 63% patients with rotator cuff tear have higher triglyceride, cholesterol, and low-density lipoprotein cholesterol levels, as opposed to only 28% in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…14 A nationwide population-based matched cohort study published in 2020 has evaluated the correlation between hyperlipidaemia and calcific tendinitis/tendinopathy utilising the same enrolled diagnostic criteria of calcific tendinitis/tendinopathy from the NHIRD database. 15 Therefore, the accuracy of diagnosis in tendinitis/tendinopathy is adequate in the NHIRD database.…”
Section: Studydesignmentioning
confidence: 99%
See 1 more Smart Citation